SOLVING HARTREE-FOCK-ROOTHAAN EQUATION USING MATLAB-BASED PROGRAM - Yudha Rabbani, Zaky
The solution to the Schrodinger Equation can be used to analyze a system. One of the most common system but has a difficult analytical solution is interacting many-body system. Hartree-Fock-Roothan can be used to simplify the equation making the solution relatively easier to solve. Hartree-Fock-Roothaan method is an iterative method thus the solution can be calculated with the help of a computer. MATLAB based program that is made in this final project is able to solve Hartree-Fock-Roothan for hydrogen molecule system. STO-2G, STO-3G, STO-4G, and STO-6G basis are used. The higher the number of Gaussian basis used, the better the resuls.t But it also increases the calculation and running time. The most efficient basis in time consumed and results accuracy used in this final project is the STO-4G basis.